The Implementation of Kindergarten Program in Multicultural Schools in Agusan Provinces, Philippines - Teresita Tranquilan (JPAIR Institutional Research Journal)
This study evaluated the implementation of the Kindergarten Education Program in Multicultural schools in the provinces of Agusan del Norte and Agusan del Sur. It looked into the context, considering the activities given to learners and the extent of implementation of the program. Qualitative and quantitative data gathering were employed. The respondents were six school heads, 12 kindergarten teachers, five parents, and 12 pupils coming from different ethnic groups. Data were analyzed using mean for quantitative and thematic analysis for qualitative. The finding showed that the implementation of the Kindergarten Program in terms of context was only fair since multicultural concepts were not explicitly stated in the Department of Education curriculum guide, which could have served as a mandate for teachers to implement concepts of multiculturalism. The extent of implementation of policies and standards stipulated by the Department of Education was highly implemented. From these findings, policies and programs were recommended to improve the quality of instruction in the Kindergarten Education Program in multicultural schools in the two Agusan provinces. It is concluded that the curriculum guide and extent of implementation as required by the Department of Education were highly implemented by the school heads and teachers; what was lacking was the explicit mandate of the Department of Education to teach the concepts, theories, and processes in the teaching of multiculturalism.